2011
DOI: 10.1007/s10562-011-0702-3
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Macroporous Structured Alumina Based Cobalt Catalysts for Fischer–Tropsch Synthesis

Abstract: Macroporous structured (MPS)-Al 2 O 3 support was synthesised from Al 2 O 3 nanoparticles with polystyrene beads as a sacrificing agent. A MPS-Al 2 O 3 with uniformly spherical and interconnected pores throughout the sample was obtained. The MPS-Al 2 O 3 was characterized and used as support for cobalt Fischer-Tropsch catalysts. Surface kinetic parameters and intrinsic activity of the catalysts were determined by steady-state isotopic transient kinetic analysis (SSITKA) at 483 K, 1.85 bar and H 2 /CO = 10. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In order to take advantage of the catalytic performance offered by α-Al 2 O 3 , a new macroporous structured (MPS-Al 2 O 3 ) support was synthesized from α-Al 2 O 3 nanoparticles to improve the supported cobalt dispersion. 128 The results obtained with this new support combine the benefits obtained of α-Al 2 O 3 and γ-Al 2 O 3 as supports, displaying similar catalytic performance compared to conventional Co/γ-Al 2 O 3 and Co/α-Al 2 O 3 catalysts, respectively. The kinetic parameters such as intrinsic rate constant and site coverage of intermediates leading to methane remains unchanged as Co/ α-Al 2 O 3 , whereas the number of active intermediates has increased substantially due to better cobalt dispersion on MPS-Al 2 O 3 .…”
Section: Study Of Fischer−tropsch Synthesis By Ssitkasupporting
confidence: 58%
“…In order to take advantage of the catalytic performance offered by α-Al 2 O 3 , a new macroporous structured (MPS-Al 2 O 3 ) support was synthesized from α-Al 2 O 3 nanoparticles to improve the supported cobalt dispersion. 128 The results obtained with this new support combine the benefits obtained of α-Al 2 O 3 and γ-Al 2 O 3 as supports, displaying similar catalytic performance compared to conventional Co/γ-Al 2 O 3 and Co/α-Al 2 O 3 catalysts, respectively. The kinetic parameters such as intrinsic rate constant and site coverage of intermediates leading to methane remains unchanged as Co/ α-Al 2 O 3 , whereas the number of active intermediates has increased substantially due to better cobalt dispersion on MPS-Al 2 O 3 .…”
Section: Study Of Fischer−tropsch Synthesis By Ssitkasupporting
confidence: 58%
“…Issues explored using SSITKA have included among others the study of mechanisms, the presence and implications of site heterogeneity, the role of chemical promoters and the effect of operation conditions on the surface coverage of intermediates. For FTS, the use of SSITKA has resulted in an improved understanding on the effect of catalyst properties (promoters [72][73][74][75][76][77][78][79][80][81][82][83], support [84][85][86][87][88][89][90], particle size etc. [91][92][93][94]) and the reaction conditions [95][96][97][98][99][100][101] on the performance.…”
Section: Approaches Of Kinetic Analysis For Ftsmentioning
confidence: 99%
“…Furthermore, they observed positive correlations between the cobalt particle size and the C 5+ selectivity and between the catalyst pore size and the C 5+ selectivity, with small variations in the cobalt site-time yields related to the chemical purity of the catalyst samples. Low-surface-area alumina (α-Al 2 O 3 ) was found to display better C 5+ selectivity compared with high-surface-area alumina (γ-Al 2 O 3 ). , A macroporous-structured (MPS) Al 2 O 3 support synthesized from Al 2 O 3 nanoparticles using polystyrene beads as a sacrificial agent seemed to combine the advantages of α-Al 2 O 3 and γ-Al 2 O 3 as support materials, with activity and selectivity comparable to those of Co/γ-Al 2 O 3 and Co/α-Al 2 O 3 , respectively . Vosoughi et al demonstrated the synthesis of mesoporous alumina using Pluronic F127 as a structure-directing agent that contributed to a high surface area and large pore volume and pore diameter of the support.…”
Section: Alumina-supported Catalystsmentioning
confidence: 98%
“…Low-surface-area alumina (α-Al 2 O 3 ) was found to display better C 5+ selectivity compared with highsurface-area alumina (γ-Al 2 O 3 ). 36,37 38 Vosoughi et al 39 demonstrated the synthesis of mesoporous alumina using Pluronic F127 as a structure-directing agent that contributed to a high surface area and large pore volume and pore diameter of the support. The structure of the thus-prepared support collapsed upon impregnation with aqueous cobalt nitrate solution, but shifting the impregnation medium from aqueous to organic (ethanol or acetone) reinstated the textural stability of the mesoporous alumina.…”
Section: Alumina-supported Catalystsmentioning
confidence: 99%
See 1 more Smart Citation